Edition et librairie françaises au Mexique au XIXè siècle - Arnulfo Uriel De Santiago Gómez (Nuevo mundo - Mundos Nuevos, 2009)
This thesis is about the French publishing and bookselling in Mexico in the 19th Century, one of the forerunners of an international market of books; its effects await further study in the field of cultural history. These consequences are related, among other things, to an increase in the editorial offer and the development of reading and writing habits. Firstly, the analysis will be focused on the definition of the “Librairie Espagnole” – a delocalized type of publishing produced in France and bound for the Iberian Peninsula and Latin America – as the registers of the Exportations de la librairie française (French bookselling’s exports) show. Secondly, the thesis describes the rise in France and the settlement in Mexico of this sector of the production of books between 1820 and 1838, with Bossange, Rosa and the Librairie Américaine. Thirdly, between 1838 and the1880’s, the integration of large “Spanish” bookstores such as Rosa and Bouret, Garnier Brothers and Hachette will be studied. Three approaches will be used for the analysis: first of all the statistical study of the publications in Spanish from 1820 to 1860, based on the Déclarations des imprimeurs de Paris (Declarations of the printers of Paris). The second approach is the revision of the records of printers and booksellers in the French National Archives, as well as the revision of the catalogues of “Spanish” booksellings. Last, the integration of a corpus of the educational and religious publishers : Catecismo of Ripalda, Cartilla (syllabus), and the Catón. This makes a sociological approach of the reading possible.